2004
DOI: 10.1002/jat.941
|View full text |Cite
|
Sign up to set email alerts
|

Role of caffeic acid phenethyl ester, an active component of propolis, against cisplatin‐induced nephrotoxicity in rats

Abstract: We have investigated the effect of caffeic acid phenethyl ester (CAPE) on cisplatin-induced nephrotoxicity in rats. Administration of a single dose of cisplatin resulted in the elevation of blood urea nitrogen and creatinine in serum, as well as nitric oxide in kidney tissue of rats. Cisplatin also caused reduction of catalase (P < 0.0001), superoxide dismutase (P = 0.149) and glutathrone peroxidase (P < 0.0001) activities in kidney tissue. Although cisplatin caused elevation in malondialdehyde levels and myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 38 publications
6
95
0
4
Order By: Relevance
“…The role of NO and RNS in cisplatin-induced nephrotoxicity has not been completely established. It has been shown that the renal content of nitrate/nitrite is increased in cisplatin-treated rats suggesting that NO is increased in these animals (25,26). The increase in renal ONOO -induced by cisplatin may be secondary to the increase in NO and O 2 production (Table II).…”
Section: Antioxidant Effect Of Carnosine Pretreatment In Ratsmentioning
confidence: 99%
“…The role of NO and RNS in cisplatin-induced nephrotoxicity has not been completely established. It has been shown that the renal content of nitrate/nitrite is increased in cisplatin-treated rats suggesting that NO is increased in these animals (25,26). The increase in renal ONOO -induced by cisplatin may be secondary to the increase in NO and O 2 production (Table II).…”
Section: Antioxidant Effect Of Carnosine Pretreatment In Ratsmentioning
confidence: 99%
“…[3,4] A number of antioxidants have been reported to reduce oxidative stress and prevent cisplatin nephrotoxicity. [5][6][7][8][9] Figure 1. Epithelial necrosis (short black arrow), cast formation, (long white arrow), and apoptotic cells (arrowhead) in the distal tubulus due to cisplatin nephrotoxicity (×200 HE; cisplatin group).…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Cisplatin is able to induce the formation of ROS and reduce the activity of antioxidant enzymes in renal tissue. [5][6][7][8][9] . The formation of excessive levels of ROS can lead to lethal or sub-lethal cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, it has been used for its antioxidant, anti-inflammatory, anti-carcinogenic, anti-viral, anti-mutagenic, and immunomodulatory activities. [6][7][8][9][10][11][12] In addition, it has been shown to protect the kidneys from ischemiareperfusion injury, 13 cisplatin- 14 and lithium-induced 15 renal damage, diabetic oxidative damage, 16 and electromagnetic field and shock wave-induced oxidative stress. 17 The current due to the properties of CAPE, a drug may be useful in the prevention of ASA-induced renal pathology.…”
Section: Introductionmentioning
confidence: 99%